Study of Palliative Care Needs among Stroke Patients Referred to Physiotherapy Centers - Tayebeh Fathollahi; Esfandyar Baljani; Monireh Rezaee moradali (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Patients with stroke need professional care and identifying the palliative needs of these people is the basis for care planning by health managers. Objectives: The present study aimed to determine the palliative care needs of stroke patients and the factors that affect these needs. Methods: The population of this cross-sectional descriptive study was the patients referred to physiotherapy centers in Mako city in 1398. A total of 160 patients were selected based on convenience sampling. The data collection tool was a two-part questionnaire. In the first part, demographic characteristics and in the second part, the questionnaire of palliative care needs in specific patients was completed. Descriptive tests, mean comparison, and Pearson correlation was used to analyze the data using SPSS software version 16. Results: The need for palliative care can vary in different fields. For example, having problems in daily life in the field of daily life activities (2.03-0.24), pain in the field of physical symptoms (2.36.07.07), dependence on others for care in the field of control over living affairs (1.72 1 0.82), tendency to talk about illness in the field of social problems, (2/71/71/71), fear of metastasis in the field of mental problems, (2.97 2 0.22), understanding the meaning of death in the field of spiritual problems (2.87  0.48), and loss of income due to diseases in the field of financial problems (2.63 89 0.89). Independent group t-test showed that the mean scores of palliative care needs of patients referred to physiotherapy centers in the two groups of men and women were not significantly different (t=92.1, p=0.057). However, One-way analysis of variance showed that the average palliative care needs of patients referred to physiotherapy centers based on their level of education had a significant difference (f=486.4, p=0.014). Conclusion: The results of the study showed that nurses and health system managers with knowledge of the needs of palliative care for patients with stroke can put training programs on discharge and disease management at home on their agenda.